Simulasi Pengaruh Diameter Roda 660 mm, 774 mm dan 860 mm Serta Variasi Kecepatan Terhadap Kriteria Nadal dan Ride Index Lintas R80 LRT Palembang (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2023)
The purpose of this study is to determine the effect of different train wheel diameters on the ride index and nadal criteria at various speeds. The analysis method uses Longitudinal Train Dynamic Universal Mechanism 9.0 simulation. Wheel diameter variations are used by using 3 different types of diameters. While the speed variation used starts from 15 km/h until the train crashes. The standard used in the simulation is the ISO 2631 standard sperling index. The results of the simulation found that wheels with smaller diameters are better at passing the R80 curve. This is evidenced at a speed of 15 km/h, a diameter of 660 mm produces horizontal and vertical ride index values of 1.2078 and 1.1282, a diameter of 774 mm of 1.8306 and 1.7078, a diameter of 860 mm of 1.8293 and 1.7068, so that there is an increase until the highest speed of 60 km / h at a diameter of 660 mm produces horizontal and vertical ride index values of 2.2744 and 2.1140, at a diameter of 774 mm of 2.2751 and 2.1140, at a diameter of 860 mm of 2.2762 and 2.1162, so that with increasing wheel diameter, the value of the ride index will be greater.